Use of Media in Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In modern society, we are witnessing the rapid penetration of mass media technologies into all spheres of life. It is safe to say that in our time the media space is an integral part of the social space and influences the formation of personality. Children receive knowledge not from textbooks, but from the media, which are always at hand. The use of modern technologies in the field of education has become not just a way to introduce diversity into the educational process, but a necessity due to the requirements of the time.